Reliability Lost, False Confessions Discovered - Godsey, Mark A. (2007)
The advent of post-conviction DNA testing in the past twenty years has spawned an Innocence Revolution, in which hundreds of Americans imprisoned or on death row for serious crimes like murder and rape have been conclusively proven innocent and released. From studying the cases of wrongful convictions, we now know that eyewitness identification is not nearly as reliable as once believed. We also know that hundreds of innocent people have been convicted through the use of junk science, such as bite mark analysis or microscopic hair comparison, which DNA testing has proven to be wildly inaccurate. Most importantly for my purposes here, we now know that suspects will confess all too often to crimes that they did not commit, leading to wrongful convictions. Of all the things that DNA has taught us about our criminal justice system, this phenomenon is perhaps the hardest to accept. The idea that a suspect would falsely confess to a crime that he did not commit seems counterintuitive and nonsensical. For centuries, constitutional confession law in the United States has been concerned with the reliability and accuracy of confessions. Prior to admission into evidence, a court in this country had to examine whether the confession at issue was accurate and trustworthy. In the 1986 case of Colorado v. Connelly, however, the United States Supreme Court suddenly subverted as a factor when considering the admissibility of a confession. Then, ironically, shortly after Connelly was decided, DNA testing started to reveal why we should be very concerned about the reliability of confessions after all. Indeed, within a decade of the Connelly decision, the false confession problem in this country had been laid bare. In this essay, taken from my talk at a symposium held by the Chapman Law Review, I attempt to shed light on this legal irony